The X-Files: Past and Present Portrayals of China's Alien “Legal System” - Randall Peerenboom (Washington University Global Studies Law Review, 2003)
In Part I of this Article, I examine the recent attempt of the prominent comparative law scholar Ugo Mattei to develop a new taxonomy that takes into consideration developments in the legal systems of China and other Asian countries in an effort to bring them into the mainstream of comparative law. While I applaud his motives and share his concerns about the need to bring Chinese legal studies into the mainstream of comparative law, I question his results. Mattei wishes to correct the Orientalist biases of prior taxonomies, but ends up imposing his own Orientalist views on Asian legal systems. In Part II of this Article, I discuss what seems to be a tendency in much foreign scholarship to portray China’s legal system in excessively negative terms and to unduly dismiss developments and trends suggesting that China is moving toward some form of rule of law. I suggest that what is needed is a more balanced approach, informed by a broader historical and comparative perspective. Part III concludes with some observations about teaching and researching Chinese law.
Keywords: Administration of justice; Comparative law; China; International